MENYOAL RELEVANSI KEBIJAKAN OTONOMI DAERAH DAN OTONOMI PENDIDIKAN DIKAJI DARI KESEJAHTERAAN - Yudi Armansyah (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2016)
Autonomy is the outcome of a decentralized system is the reform agenda of the Indonesian nation. Decentralization touch the whole life of the nation, including educational programs and activities. The education sector is experiencing a transition from the management arrangements and the delivery of education regulated by the district / city, so as to adjust the content of teaching adapted to direct development. Autonomous education is not just about the handover of authority to the education unit to organize and manage programs and educational activities independently and be transparent and accountable, but make education effective in the development of the local area to achieve a prosperous society.